2018
DOI: 10.1371/journal.pone.0194283
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle magnetic resonance biomarkers correlate with function and sentinel events in Duchenne muscular dystrophy

Abstract: ObjectiveTo provide evidence for quantitative magnetic resonance (qMR) biomarkers in Duchenne muscular dystrophy by investigating the relationship between qMR measures of lower extremity muscle pathology and functional endpoints in a large ambulatory cohort using a multicenter study design.MethodsMR spectroscopy and quantitative imaging were implemented to measure intramuscular fat fraction and the transverse magnetization relaxation time constant (T2) in lower extremity muscles of 136 participants with Duchen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 42 publications
(69 reference statements)
3
62
0
1
Order By: Relevance
“…Third, we found that the fat fraction and the functional ability of the diaphragm were strongly correlated. Prior studies have found high degrees of correlation between MRI measures of fat fraction of quickly degenerating proximal muscles and ambulatory function, measured using the 10‐m walk/run, the climb four stairs, supine to stand, and 6‐minute walk tests . With respect to these studies, we directly related the fat fraction increase of the diaphragm to its excursion function; thus, the structure–function relationship was investigated free from any compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we found that the fat fraction and the functional ability of the diaphragm were strongly correlated. Prior studies have found high degrees of correlation between MRI measures of fat fraction of quickly degenerating proximal muscles and ambulatory function, measured using the 10‐m walk/run, the climb four stairs, supine to stand, and 6‐minute walk tests . With respect to these studies, we directly related the fat fraction increase of the diaphragm to its excursion function; thus, the structure–function relationship was investigated free from any compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found high degrees of correlation between MRI measures of fat fraction of quickly degenerating proximal muscles and ambulatory function, measured using the 10-m walk/run, the climb four stairs, supine to stand, and 6-minute walk tests. 15,[37][38][39] With respect to these studies, we directly related the fat fraction increase of the diaphragm to its excursion function; thus, the structure-function relationship was investigated free from any compensatory mechanisms. Studies performed by using ultrasonography (US) showed a progressive diaphragm atrophy with age and reduced excursion.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sectional studies in DMD have shown strong correlations of quantitative fat fraction and T2 values with the 6‐minute walk test . Another recent study in DMD patients used MRI‐derived fat fractions and T2 values to classify patients according to loss of motor milestones such as the ability to climb stairs and stand from supine . Other studies have sought to establish a correlation between imaging biomarkers and disease‐specific clinical scales .…”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of using MRS rather than T2‐weighted imaging is that the contributions of fat and free water to the T2 signal can be more clearly partitioned by using MRS. Researchers using 1 H MRS in DMD have been able to detect larger lipid metabolite peaks associated with smaller water peaks in older age groups; these studies have also demonstrated that fat fractions calculated from MRS correlate significantly with muscle strength and functional endpoints …”
Section: Evaluating Intramuscular Fatmentioning
confidence: 95%
See 1 more Smart Citation